Sensory and emotional responses to deep pressure stimulation at myofascial trigger points: a pilot study - Lee, Seoyoung; Moon, Heeyoung; Ryu, Yeonhee; Lee, In-Seon; Chae, Younbyoung (Frontiers in Neuroscience, 2023)
Objective: Although manual pressure, such as that used during a massage, is often associated with pain, it can simultaneously be perceived as pleasant when applied to certain body areas. We hypothesized that stimulation of myofascial trigger points (TPs) leads to simultaneous pain and pleasure. TPs are hyperirritable points located in the taut band of the skeletal muscle. Method: In this study, we measured the muscle tone, muscle stiffness, and pressure pain threshold of TPs and control points in the left brachioradialis muscle of 48 healthy participants. We also applied deep compression to the two points and collected subjective data on pain, pleasantness, unpleasantness, and relief. Result: Greater muscle stiffness was observed in the TPs versus control points (t = 6.55, p < 0.001), and the pain threshold was significantly lower in the TPs (t = -6.21, p < 0.001). Unpleasantness ratings after deep compression were significantly lower in the TPs compared with control points (t = -2.68, p < 0.05). Participants experienced greater relief at the TPs compared with control points (t = 2.01, p < 0.05), although the perceived pain did not differ between the two types of points. Conclusion: We compared the properties of TPs and control points, and found that deep compression at TPs was associated with higher muscle tone and stiffness, lower unpleasantness ratings, and higher relief ratings compared with the control points. These findings suggest that, at least for some TPs, pain and pleasantness are simultaneously elicited by deep pressure stimulation.